Smartphones & microfluidics: Marriage for the future - Hárendarčíková, Lenka; Petr, Jan (Electrophoresis, 2018)
Smartphones have become widely recognized as a very interesting detection and controlling tool in microfluidics. They are portable devices with built-in cameras and internal microprocessors which carry out image processing. In this case, the external computers are not needed and phones can provide fast and accurate results. Moreover, the connectivity of smartphones gives the possibility to share and provide real-time results when needed, whether in health diagnostics, environmental monitoring, immunoassays or food safety. Undoubtedly, the marriage of smartphones and microfluidics has a brilliant future in building low cost and easily operable systems for analysis in the field, realizing the idea of people's "smartlife". The aim of this review is to present and summarize the main advantages and disadvantages of the use of smartphones as well as to take a closer look at some novel achievements published during the last couple of years. In the next paragraphs, readers will find specific uses of a combination of smartphones and microfluidics such as water analysis, health analysis (virus and bacteria detection), and measurement of physical properties or smartphone liquid control in polymer devices.
Keywords: Forecasting; předpověď; Microfluidics; Humans; lidé; chytrý telefon; Smartphone; mikrofluidika